Learning Activities in Physics Using Students Worksheet Based on Predict-Observe-Explain (POE) - Dewi Fairuz Zulaikha; Pujianto Pujianto; Yusman Wiyatmo (STKIP Singkawang, 2021)
This research aims to describe students learning activities through the implementation of students worksheets based on POE. This study was descriptive qualitative research. The research was conducted in one of the Islamic Senior High School in Bantul, Yogyakarta on Circular Motion material. The research subject was determined through random sampling. The number of subjects in this research consisted of 26 students in the first year. Data were collected using an observation sheet in 3 meetings observed by two persons and the interview. The results of the analysis obtained are expressed in terms of percentages and then interpreted in the form of scientific narratives. Data analysis results show that the students’ worksheet based on POE can be used to enhance students’ learning activities, especially in visual activities, oral activities, writing activities, motor activities, and mental activities with the most dominant activities is writing activities, and the weakest one is oral activities. Students feel that using students’ worksheets based on predict-observe-explain makes them involved directly in the demonstration or the practicum, can create their curiosity, make they even more seriously in the study, increase the interest in studying physics and help each other with their friends. But, the students’ confidence and speaking ability must be the concern, so students are not reluctant to share their idea in front of the class.